Aktivitas Antioksidan Ekstrak Batang Tanaman Wungu (Graptophyllum pictum (Linn) Griff) Menggunakan Metode FRAP - Harwati, Wiwik; Mahfur (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2024)
The wungu plant is a type of ornamental plant originating from Papua New Guinea and Polynesia which contains flavonoid compounds. This study aims to determine the antioxidant activity of wungu plant stem extract (Graptophyllum pictum (Linn) Griff) using the FRAP method. Identification of flavonoids using color reagents and antioxidant testing using the FRAP method. Wungu plant stem extract was made into a series of solutions with concentrations of 50, 75, 100, 125 and 150 ppm, while quercetin as a comparison was made with concentrations of 2, 4, 6, 8 and 10 ppm. The results of flavonoid identification showed that the sample contained flavonoids. The results of antioxidant activity in the comparison standard quercetin had an IC50 value of 1,62 ppm, while the wungu plant stem extract had an IC50 value of 13.13 ppm. From these results it can be concluded that the wungu plant stem extract using the FRAP method has very strong antioxidant activity with an IC50 value of 13,13 ppm.